The Relationship Between Dietary Patterns and Sleep Patterns on Pain in Dyspepsia Patients at the Tangkit Muaro Jambi Community Health Centre in 2025 - Imran, Suryadi; Aguspairi; Julfiyanti, Ermi Eka (Program Studi Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2025)
Background: Dyspepsia is the most common digestive health problem. Dyspepsia is a syndrome of symptoms commonly found in the community, characterised by pain or discomfort in the upper abdomen or pit of the stomach. Several factors cause pain in dyspepsia patients, including irregular eating patterns and poor sleeping patterns. Objective: This study aims to investigate the relationship between eating patterns and sleep patterns in relation to pain in patients with dyspepsia. Method: This study is a quantitative analytical study with a cross-sectional approach. The population consists of all dyspepsia patients at the Tangkit Muaro Jambi Community Health Centre, totalling 31 patients. A sample of 31 people was taken using a total sampling technique. This study was conducted at the Tangkit Muaro Jambi Community Health Centre in May 2025. Data collection was carried out using a questionnaire. Data were analysed univariately and bivariately using the chi-square test. Results:The results showed that most respondents had poor eating habits (74.2%), poor sleep patterns (51.6%), and moderate dyspepsia pain (45.2%). Conclusions: There was a relationship between eating patterns (p = 0.000) and sleep patterns (p = 0.000) with pain in dyspepsia patients at the Tangkit Muaro Jambi Community Health Centre, with a p-value < 0.05. These findings indicate that diet and sleep patterns cause pain in dyspepsia patients. Health workers should prioritize community health education about diet, sleep, and dyspepsia.